2018
DOI: 10.17844/jphpi.v21i2.23090
|View full text |Cite
|
Sign up to set email alerts
|

KARAKTERISTIK IKAN ASIN KAMBING-KAMBING (Canthidermis maculata) DENGAN PENGGARAMAN KERING

Abstract: Ikan kambing-kambing (Canthidermis maculata) merupakan ikan demersal yang potensial. Salah satu<br />produk olahan dari ikan kambing-kambing adalah ikan asin. Tujuan dari penelitian ini adalah menentukan<br />pengaruh konsentrasi garam dan lama penggaraman terhadap karakteristik ikan asin yang dihasilkan.<br />Penelitian dilakukan dalam dua tahap, tahap pertama adalah preparasi bahan baku tahap kedua pembuatan<br />ikan asin menggunakan metode penggaraman kering dengan konsentrasi garam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…Fish will last longer than fish that do not use salt (Patang & Yunarti, 2014). The results of this study are following previous studies which showed that salt concentration and salting time had a significant effect on the characteristics of salted fish, which included salt content, water content and total microbes, a salt concentration of 15% with a salting time of 24 hours was the best treatment for salted fish products (Akbardiansyah, Desniar, & Uju, 2018). The addition of salt with different concentrations in the drying process of fish affects the water content, protein, amino acids, and fish TPC (Bahmid et al, 2019;Puspitasari et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…Fish will last longer than fish that do not use salt (Patang & Yunarti, 2014). The results of this study are following previous studies which showed that salt concentration and salting time had a significant effect on the characteristics of salted fish, which included salt content, water content and total microbes, a salt concentration of 15% with a salting time of 24 hours was the best treatment for salted fish products (Akbardiansyah, Desniar, & Uju, 2018). The addition of salt with different concentrations in the drying process of fish affects the water content, protein, amino acids, and fish TPC (Bahmid et al, 2019;Puspitasari et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…The longer the drying time for salted fish products, the lower the water content value of the product. So it takes a higher temperature so that the drying airflow is faster and the drying process takes place (Akbardiansyah et al, 2018). The implication of this research, it is hoped that anglers who want to increase the production of fishery products by preserving one of them with the fish drying method to produce good, quality, and competitive salted fish in the market, to pay attention to factors such as the thickness of fish meat, temperature and drying time to obtain good results.…”
Section: Discussionmentioning
confidence: 93%
“…So the results of drying fish that have been done are different. Fish drying is one of the easiest, cheapest, and oldest preservation methods (Akbardiansyah, Desniar, & Uju, 2018;Yuwana et al, 2019). Drying aims to reduce the water content in the fish.…”
Section: Discussionmentioning
confidence: 99%
“…This proves that boiled crab has a good acceptance by consumers and the rate of quality deterioration tends to be slow. According to Junianto [10], organoleptic or sensory values are influenced by the freshness and quality of fish. During the quality deterioration process, there will be a process of changing chemical and physical composition that has an impact on the organoleptic value, which starts after the fish dies with prerigor, rigor mortis, and post-rigor stages.…”
Section: Sensory Valuementioning
confidence: 99%